(untitled) (Tạp chí Y học Cộng đồng, 2022)
Inflammatory pseudotumor of the liver (IPTL) is a rare benign lesion characterized by chronic infiltration of inflammotory cells and an areas of fibrosis that sometimes mimics a malignant lesion, first reported by Pack and Baker in 1953. The etiology and pathogy still remain unknown. Clinical and laboratory features are not specific. The treatment attitude is still controversial. We report 3 cases of IPTL who were treated surgically with preoperative diagnosis of ruptured liver abscess or a malignant liver tumor. The postoperative patient was safe and the pathological results were inflammotory pseudotumor of the liver. Conclusion: IPTL is a benign lesion that can be confused with other diagnoses of the liver. The treatment of choice is still surgical resection, and this is especially true for patients with severe symptoms or an indeterminate diagnosis.